2019
DOI: 10.18203/2319-2003.ijbcp20194781
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of efficacy and safety of ketoprofen patch versus diclofenac patch as post-operative analgesic in hysterectomy patients

Abstract: Background: The objective of the study was to compare the efficacy and safety of ketoprofen patch versus diclofenac patch as post-operative analgesic in hysterectomy patients.Methods: The study was a prospective, single blind, randomized, comparative interventional clinical study conducted in a tertiary care hospital. Sixty female patients were randomly allocated to receive either ketoprofen or diclofenac patch 1 hour prior to the hysterectomy. Pain was assessed postoperatively after an interval of every four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Similar results were also observed by Jadhav et al and Bhargava et al [2,8]. TDDS provided a continual absorption of the drug across the dermis, thus allowing for consistent serum drug levels with increased tissue concentration and low plasma concentration [24]. The present study demonstrated the superior analgesic efficacy of ketoprofen over diclofenac transdermal patches.…”
Section: Discussionsupporting
confidence: 91%
“…Similar results were also observed by Jadhav et al and Bhargava et al [2,8]. TDDS provided a continual absorption of the drug across the dermis, thus allowing for consistent serum drug levels with increased tissue concentration and low plasma concentration [24]. The present study demonstrated the superior analgesic efficacy of ketoprofen over diclofenac transdermal patches.…”
Section: Discussionsupporting
confidence: 91%
“…The results are supported by a study by Rani et al . [ 13 ] who compared the two patches in patients who underwent a hysterectomy. They concluded that transdermal patches are cause less discomfort as compared to traditional routes of drug delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Ketoprofen (KET) is one of the most common NSAIDs (Nonsteroidal anti-inflammatory drugs) used for relieving pain in many acute and chronic conditions as musculoskeletal, tendinitis, strain, sprain, trauma, and arthritis [ 1 , 2 ]. However, its efficacy, especially in topical therapies, is impaired due to both the very poor water solubility (KET is labeled in class II of the biopharmaceutics classification system, BCS) and photochemical instability [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%